Unmanned Aerial Vehicles for Real-Time Vegetation Monitoring in Antarctica: A Review - Lockhart, Kaelan; Sandino, Juan; Amarasingam, Narmilan; Hann, Richard; Bollard, Barbara; Gonzalez, Felipe (Remote Sensing, 2025)
The unique challenges of polar ecosystems, coupled with the necessity for high-precision data, make Unmanned Aerial Vehicles (UAVs) an ideal tool for vegetation monitoring and conservation studies in Antarctica. This review draws on existing studies on Antarctic UAV vegetation mapping, focusing on their methodologies, including surveyed locations, flight guidelines, UAV specifications, sensor technologies, data processing techniques, and the use of vegetation indices. Despite the potential of established Machine-Learning (ML) classifiers such as Random Forest, K Nearest Neighbour, and Support Vector Machine, and gradient boosting in the semantic segmentation of UAV-captured images, there is a notable scarcity of research employing Deep Learning (DL) models in these extreme environments. While initial studies suggest that DL models could match or surpass the performance of established classifiers, even on small datasets, the integration of these advanced models into real-time navigation systems on UAVs remains underexplored. This paper evaluates the feasibility of deploying UAVs equipped with adaptive path-planning and real-time semantic segmentation capabilities, which could significantly enhance the efficiency and safety of mapping missions in Antarctica. This review discusses the technological and logistical constraints observed in previous studies and proposes directions for future research to optimise autonomous drone operations in harsh polar conditions.
Keywords: Antarktis; droner; dyp læring; fjernmåling; kartlegging; kunstig intelligens (KI); kybernetikk; maskinlæring; teknologi; vegetasjon

Early aerial expedition photos reveal 85 years of glacier growth and stability in East Antarctica - Dømgaard, Mads; Schomacker, Anders; Isaksson, Elisabeth; Millan, Romain; Huiban, Flora; Dehecq, Amaury; Fleischer, Amanda; Moholdt, Geir; Andersen, Jonas K.; Bjørk, Anders A. (Nature Communications, 2024)
During the last few decades, several sectors in Antarctica have transitioned from glacial mass balance equilibrium to mass loss. In order to determine if recent trends exceed the scale of natural variability, long-term observations are vital. Here we explore the earliest, large-scale, aerial image archive of Antarctica to provide a unique record of 21 outlet glaciers along the coastline of East Antarctica since the 1930s. In Lützow-Holm Bay, our results reveal constant ice surface elevations since the 1930s, and indications of a weakening of local land-fast sea-ice conditions. Along the coastline of Kemp and Mac Robertson, and Ingrid Christensen Coast, we observe a long-term moderate thickening of the glaciers since 1937 and 1960 with periodic thinning and decadal variability. In all regions, the long-term changes in ice thickness correspond with the trends in snowfall since 1940. Our results demonstrate that the stability and growth in ice elevations observed in terrestrial basins over the past few decades are part of a trend spanning at least a century, and highlight the importance of understanding long-term changes when interpreting current dynamics.
Article number: 4466
Keywords: Antarktis; Thorshavn ekspedisjon; flyfotografering; geografi; glasiologi; kartlegging; klimaendringer; klimatologi; kryosfæren; topografi

BVLOS UAV missions for vegetation mapping in maritime Antarctic - Zmarz, Anna; Karlsen, Stein Rune; Kycko, Marlena; Korczak-Abshire, Małgorzata; Gołębiowska, Izabela; Karsznia, Izabela; Chwedorzewska, Katarzyna (Frontiers in Environmental Science, 2023)
Polar areas are among the regions where climate change occurs faster than on most of the other areas on Earth. To study the effects of climate change on vegetation, there is a need for knowledge on its current status and properties. Both classic field observation methods and remote sensing methods based on manned aircraft or satellite image analysis have limitations. These include high logistic operation costs, limited research areas, high safety risks, direct human impact, and insufficient resolution of satellite images. Fixed-wing unmanned aerial vehicle beyond the visual line of sight (UAV BVLOS) missions can bridge the scale gap between field-based observations and full-scale airborne or satellite surveys. In this study the two operations of the UAV BVLOS, at an altitude of 350 m ASL, have been successfully performed in Antarctic conditions. Maps of the vegetation of the western shore of Admiralty Bay (King George Island, South Shetlands, Western Antarctic) that included the Antarctic Specially Protected Area No. 128 (ASPA 128) were designed. The vegetation in the 7.5 km2 area was mapped in ultra-high resolution (<5 cm and DEM of 0.25 m GSD), and from the Normalized Difference Vegetation Index (NDVI), four broad vegetation units were extracted: “dense moss carpets” (covering 0.14 km2, 0.8% of ASPA 128), “Sanionia uncinata moss bed” (0.31 km2, 1.7% of ASPA 128), “Deschampsia antarctica grass meadow” (0.24 km2, 1.3% of ASPA 128), and “Deschampsia antarctica–Usnea antarctica heath” (1.66 km2, 9.4% of ASPA 128). Our results demonstrate that the presented UAV BVLOS–based surveys are time-effective (single flight lasting 2.5 h on a distance of 300 km) and cost-effective when compared to classical field-based observations and are less invasive for the ecosystem. Moreover, unmanned airborne vehicles significantly improve security, which is of particular interest in polar region research. Therefore, their development is highly recommended for monitoring areas in remote and fragile environments.
Keywords: Sørishavet; kartlegging; logistikk; teknologi; vegetasjon

Dronning Maud Land: der ingen skulle tru at det var fjell ... - Engeland, Sveinung; Engeland, Sveinung (Høyde over havet : hvordan fjellene våre ble målt og satt på kartet, 2021)
Keywords: Dronning Maud Land; ekspedisjoner; geografi; kartlegging; oppdagelsesreiser

Geological mapping of Norway's least explored mountains - Elvevold, Synnøve; Myhre, Per Inge; Engvik, Ane K; Jacobs, Joachim (Fram forum, 2019)
Keywords: Dronning Maud Land; ekspedisjoner; geologi; kartlegging; nunataker

Sett fra luften - Berg, Thomas Reinertsen (Verdensteater : kartenes historie, 2017)
Keywords: ekspedisjoner; flyfotografering; karthistorie; kartlegging; kartografi

Autonomous observing platform CO2 data shed new light on the Southern Ocean carbon cycle - Olsen, Are (Global Biogeochemical Cycles, 2017)
While the number of surface ocean CO2 partial pressure (pCO2) measurements has soared the recent decades, the Southern Ocean remains undersampled. Williams et al. (2017, https://doi.org/10.1002/2016GB005541) now present pCO2 estimates based on data from pH-sensor equipped Bio-Argo floats, which have been measuring in the Southern Ocean since 2014. The authors demonstrate the utility of these data for understanding the carbon cycle in this region, which has a large influence on the distribution of CO2 between the ocean and atmosphere. Biogeochemical sensors deployed on autonomous platforms hold the potential to shape our view of the ocean carbon cycle in the coming decades.
Keywords: Sørishavet; atmosfæren; biogeokjemi; karbon syklus; karbondioksid; kartlegging; klimaendringer; klimatologi; observasjoner

The Mapping of Antarctica - Pedersen, Jakob Søndergård; Curtis, Philip (The Map House, 2012)
Keywords: Antarktis; ekspedisjoner; kart; kartlegging; kartografi; oppdagelsesreiser

Veivisere under sydkorset - Walsøe, Jan Oskar (Sophie Borchgrevink Nordrum og Ivar O. Nordrum, 2012)
Keywords: Antarktis; Carsten Egeberg Borchgrevink; Southern Cross; Sydpolen; ekspedisjonen; ekspedisjoner; kartlegging; oppdagelsesreiser; polarområdene

Nature environment map: H.U. Sverdrupfjella, Dronning Maud Land, East Antarctica - Elvevold ed., Synnøve; Ohta ed., Yoshihide; Polarinstitutt, Norsk (Norwegian Polar Institute, 2010)
Publication Title: Temakart ISBN: 28
Keywords: Dronning Maud Land; geologi; glasiologi; kartlegging

Two decades of geological mapping and research in Heimefrontfjella, Dronning Maud Land, Antarctica - Weber, Klaus; Jacobs, Joachim (Polarforschung, 2009)
Heimefrontfjella is a strongly segmented NE–SW trending mountain range some 130 km long with a maximum width of about 30 km. The range takes the form of a prominent escarpment, which rises more than 1000 m above the ice plains to the northwest. The maximum elevation reaches 2700 m above sea level. Since its discovery during the German Antarctic Expedition 1938/39, very few scientists had visited Heimefrontfjella by 1985. During the mid 1960s two British geologists had visited the Heimefrontfjella and provided a geological overview of the area. Thereafter, detailed geological investigations became possible with the establishment of the Georg von Neumayer Station on the Ekström ice shelf in 1981, situated some 450 km north of Heimefrontfjella. Since then, the Georg von Neumayer Station has provided a logistical base for multidisciplinary research programs within the Atlantic sector of East Antarctica.
Publisher: Alfred-Wegener-Institut für Polar- und Meeresforschung und Deutsche Gesellschaft für Polarforschung Place: Bremerhaven, Germany ISBN: 2190-1090
Keywords: Dronning Maud Land; ekspedisjoner; geologi; kartlegging

Fast-ice distribution in East Antarctica during 1997 and 1999 determined using RADARSAT data - Giles, A Barry; Massom, Robert A; Lytle, Victoria I (Journal of Geophysical Research: Oceans, 2008)
We present the first detailed maps of fast ice around East Antarctica (75°E–170°E), using an image correlation technique applied to RADARSAT ScanSAR images from November in 1997 and 1999. This method is based upon searching for, and distinguishing, correlated regions of the ice-covered ocean which remain stationary, in contrast to adjacent moving pack ice. Within the overlapping longitudinal range of ∼86°E–150.6°E, the total fast-ice area is 141,450 km2 in 1997 and 152,216 km2 in 1999. Calibrated radar backscatter data are also used to determine the distribution of two fast-ice classes based on their surface roughness characteristics. These are “smooth” fast ice (−25.4 dB to −13.5 dB) and “rough” fast ice (−13.5 dB to −2.5 dB). The former comprises ∼67% of the total area, with rough fast ice making up the remaining ∼33%. An estimate is made of fast-ice volume, on the basis of fast-ice type as a proxy measure of ice thickness and area. Results suggest that although fast ice forms 2–16% of the total November sea ice area for this sector of East Antarctica in 1997 and 1999 (average 8.3% across maps), it may comprise 6–57% of the total ice volume (average ∼28% across maps). Grounded icebergs play a key role in fast-ice distribution in all regions apart from 150°E–170°E. These are “snapshot” estimates only, and more work is required to determine longer-term spatiotemporal variability.
Keywords: Sørishavet; batymetri; biologi; havis; kartlegging; landfast is; satellite bilder; sjøis; økologi

Den Norske Antarktisekspedisjonen 1956-60 : Norway Station (Fimbul) - Henriksen, Hans-Martin (2007)
Keywords: Antarktistraktaten 1959; Den norske antarktisekspedisjonen 1956–1960; Det internasjonale geofysiske år 1957/58; Dronning Maud Land; IGY 1957-58; NAX; geologi; glasiologi; jordmagnetiske målinger; kartlegging; meteorologi; overvintring; tidevannsmålinger

Widerøe kartlegger i Antarktis - Widerøe, Turi (Perspektiv, 2007)
Keywords: Antarktis; Dronning Maud Land; Lars Christensen; Norvegia ekspedisjoner; flyhistorie; hvalfangst; kartlegging

Is, fly og skip : oppdagelse og kartlegning med fly i Øst-Antarktis 1929-1939 - Widerøe, Turi; Drivenes, Einar-Arne (Universitetet i Tromsø, 2006)
Publication Title: Institutt for historie. Det samfunnsvitenskapelige fakultet
Keywords: Antarktis; ekspedisjoner; fly; fotogrammetri; geografi; historie; hvalfangst; kartlegging; kartografi; oppdagelsesreiser

Environmental aspects of the 2000/2001 Norwegian Antarctic research expedition - Njåstad, Birgit (Norwegian Antarctic Research Expedition (NARE) 2000/2001, 2002)
Keywords: Antarktistraktaten; Dronning Maud Land; NARE 2000/01; avfallshåndtering; fauna; flora; forurensning; kartlegging; miljøvern

Sea ice concentration off Dronning Maud Land, Antarctica - Pavlova, Olga; Winther, Jan-Gunnar (Norsk Polarinstitutt, 2002)
This project was undertaken by the Norwegian Polar Institute for the Norwegian Petroleum Directorate (Oljedirektoratet) as support for planning of marine geophysical surveys offshore from Dronning Maud Land (DML), Antarctica. The project was carried out by scientists Olga Pavlova and Jan-Gunnar Winther at the Norwegian Polar Institute under the direction of Morten Sand at the Norwegian Petroleum Directorate. The main objectives of the project were to: a) calculate 10-day average historical (i.e., 1978-1996) sea ice concentrations off DML for the months of December through April b) identify the minimum and maximum sea ice extent occurring in the period 1978-1996 c) present the above information graphically. Daily microwave satellite data covering the period 1978-1996 with 25 x 25 km spatial resolution were used as basis for this study (see text below for description of data set).
Publication Title: Norsk polarinstitutt. Rapportserie
Keywords: Dronning Maud Land; havis; kartlegging; marin geofysikk; meteorologi; sjøis

A local geoid in Dronning Maud Land - The NARE 96/97 Geoid - Eiken, Trond; Omang, Ove Christian Dahl; Øvstedal, Ola (IGeS Bulletin, 2001)
The main purpose of the present paper is to estimate the orthometric height of the Global Positioning System (GPS)-station at Troll, Dronning Maud Land, Antarctica. Located at approximately 1300 m above sea level Troll has been connected to the Geodetic Infrastructure forAntarctica (GIANT)-network, but it’s orthometric height remains undetermined. A local geoid has been determined based on gravity-, tidal- and GPS-observations and available gravity anomalies. Information about the ice-thickness has been included in the terrain model. Based on tidal measurements the mean sea level was determined in Jutulgryta, a rift zone in the Fimbulisen ice shelf. Several gravity- and GPS-stations were measured between the two points (Jutulgryta andTroll), a distance of approximately 100 km.
Keywords: Dronning Maud Land; NARE 1996/97; Troll forskningsstasjon; geodesi; kartlegging

C.A. Larsen - Pioneer of the Antarctic ocean - Devig, Thor N (Norwegian maritime explorers and expeditions : over the past thousand years, 1999)
Keywords: Antarktis; Carl Anton Larsen; Nordmenn; Sørishavet; historie; hvalfangst; kartlegging; oppdagelsesreiser; pelagisk; polarekspedisjoner

A local geoid in Dronning Maud Land - Eiken, Trond; Omang, Ove Christian Dahl; Øvstedal, Ola (24th General Assembly European Geophysical Society, 1999)
The main purpose of the present paper is to estimate the orthometric height of the GPS-station at Troll, Dronning Maud Land, Antarctica. Located at approximately 1300 m Troll has been connected to the GIANT-network, but it's orthometric height remains undetermined. A local geoid has been determined based on available gravity anomalies and vertical angle mesurements. Information about the ice-thickness has been included in the terrain model. Based on tidal measurements the mean sea level was determined in Jutulgryta, a rift zone in the Fimbulisen ice shelf. Several gravity- and GPS-stations were measured between the two points (Jutulgryta and Troll), a distance of approximately 100 km.
Keywords: Dronning Maud Land; NARE ekspedisjoner; Troll forskningsstasjon; geodesi; kartlegging

Kvitkuven: Kronprinsesse Märtha Kyst (Norsk Polarinstitutt, 1997)
Pages: Blad/Sheet B6S Place: Oslo
Keywords: Dronning Maud Land; geografi; kartlegging; satellite bilder

Vestfjella Aust: Maudheimvidda (Norsk Polarinstitutt, 1997)
Pages: Blad/Sheet C7S Place: Oslo
Keywords: Dronning Maud Land; geografi; kartlegging; satellite bilder

Vestfjella Vest: Maudheimvidda (Norsk Polarinstitutt, 1997)
Pages: Blad/Sheet B7S Place: Oslo
Keywords: Dronning Maud Land; geografi; kartlegging; satellite bilder

Ahlmannryggen: Maudheimvidda (Norsk Polarinstitutt, 1996)
Pages: Blad/Sheet G5S Place: Oslo
Keywords: Dronning Maud Land; geografi; kartlegging; satellite bilder

Jutulstraumen: Maudheimvidda (Norsk Polarinstitutt, 1996)
Pages: Blad/Sheet G6S Place: Oslo
Keywords: Dronning Maud Land; geografi; kartlegging; satellite bilder

Using multiple data sources to enhance photogrammetry for mapping Antarctic terrain - Fox, Adrian J (Polar Research, 1995)
Keywords: Antarktis; flyfoto; geografi; kartlegging; luftfoto; satellittbilder

Nature environment map: Gjelsvikfjella and Western Mühlig-Hofmannfjella, Dronning Maud Land, Antarctica - Høgvard, K (Norsk Polarinstitutt, 1993)
Pages: Blad/Sheet 1 Publication Title: Norsk Polarinstitutt Temakart Nr. 24 Place: Oslo
Keywords: Dronning Maud Land; NARE 1984/85; NARE 1989/90; geografi; kartlegging

Jutulsessen: Fimbulheimen (Norsk Polarinstitutt, 1992)
Place: Oslo
Keywords: Dronning Maud Land; Troll forskningsstasjon; geografi; kartlegging; satellite bilder

H.U. Sverdrupfjella: Fimbulheimen (Norsk Polarinstitutt, 1991)
Pages: Blad H6S Place: [Oslo]
Keywords: Dronning Maud Land; geografi; kartlegging; satellite bilder

Jutulgryta: Fimbulheimen (Norsk Polarinstitutt, 1991)
Pages: Blad/Sheet H5S Place: Oslo
Keywords: Dronning Maud Land; geografi; kartlegging; satellite bilder

Mühlig-Hofmannfjella Nord: Fimbulheimen (Norsk Polarinstitutt, 1991)
Pages: Blad/Sheet J5S Place: Oslo
Keywords: Dronning Maud Land; geografi; kartlegging; satellite bilder

Mühlig-Hofmannfjella Sør: Fimbulheimen (Norsk Polarinstitutt, 1991)
Pages: Blad/Sheet J6S Place: Oslo
Keywords: Dronning Maud Land; geografi; kartlegging; satellite bilder

Fractal Texture Signature estimated by Multiscale LIT-SNN and MAX-MIN Operators on LANDSAT-5 MSS Images of the Antarctic - Albregtsen, Fritz (Proceedings of the 6th Scandinavian Conference on Image Analysis: Oulu, June 19-22, 1989, 1989)
Keywords: Antarktis; kartlegging; kartografi; satellite bilder

Satellittkartlegging ved Norsk Polarinstitutt - Amlien, Jostein (Kart og plan, 1989)
Publisher: Fagbokforl.
Keywords: Dronning Maud Land; fotogrammetri; kartlegging; kartografi; satellite bilder

Heimfrontfjella Nord: Maudheimvidda (Norsk Polarinstitutt, 1988)
Pages: Blad/Sheet D8 Place: Oslo
Keywords: Dronning Maud Land; flyfoto; geografi; kartlegging; luftfoto

Heimfrontfjella Sør: Maudheimvidda (Norsk Polarinstitutt, 1988)
Pages: Blad/Sheet D9 Place: Oslo
Keywords: Dronning Maud Land; flyfoto; geografi; kartlegging; luftfoto

Namnemanus Peter I Øy (Norsk Polarinstitutt, 1988)
Pages: Vedtak sak 125, 21.1.1988. Namnekomiteen
Keywords: Peter I. Øy; geografi; kartlegging

Bildebehandlingsmetoder i fremstilling av digitale satelittkart over Antarktis - Davidsen, Dag (Universitetet i Oslo, 1988)
Publication Title: Bildebehandlingslaboratoriet, Institutt for informatikk ISBN: 8274760352
Keywords: Antarktis; informatikk; kartlegging; kartografi; satellite bilder

Ekspedisjonen til Peter I Øy - Svendsen, Knut; Eiken, Trond (Polarboken, 1988)
Keywords: Peter I. Øy; ekspedisjoner; kartlegging; naturvitenskap

Flichnerfjella Nord: Fimbulheimen (Norsk Polarinstitutt, 1984)
Pages: Blad/Sheet K5 Place: Oslo
Keywords: Dronning Maud Land; geografi; kartlegging; satellite bilder

Polar mapping using LANDSAT data : Svalbard and Dronning Maud Land : final report - Ødegaard, Helge; Helle, Sigurd G (IBM; Norsk Polarinstitutt, 1982)
Keywords: Dronning Maud Land; fjernmåling; kartlegging; kartografi; satellite bilder

Forposten: Fimbulheimen (Norsk Polarinstitutt, 1975)
Pages: Blad/Sheet N5 Place: Oslo
Keywords: Den norske antarktisekspedisjonen 1956-60; Dronning Maud Land; flyfoto; geografi; kartlegging; luftfoto

Sarkofagen: Fimbulheimen (Norsk Polarinstitutt, 1975)
Blad/Sheet N6
Keywords: Den norske antarktisekspedisjonen 1956-60; Dronning Maud Land; flyfoto; geografi; kartlegging; luftfoto

Schirmacheroasen: Fimbulheimen / Prinsesse Astrid Kyst (Norsk Polarinstitutt, 1973)
Pages: Blad/Sheet L4
Keywords: Den norske antarktisekspedisjonen 1956-60; Dronning Maud Land; flyfoto; geografi; kartlegging; luftfoto

Starheimtind: Fimbulheimen / Prinsesse Astrid Kyst (Norsk Polarinstitutt, 1973)
Blad/Sheet M4
Keywords: Den Norske Antarktisekspedisjonen 1956-60; Dronning Maud Land; flyfoto; geografi; kartlegging; luftfoto

Annandagstoppane. Maudheimvidda (Norsk Polarinstitutt, 1972)
Pages: Blad E6 Place: Oslo
Keywords: Dronning Maud Land; geografi; kartlegging

Vestfjella Aust: Maudheimvidda (Norsk Polarinstitutt, 1972)
Pages: Blad/Sheet C7 Place: Oslo
Keywords: Dronning Maud Land; Maudheimekspedisjonen; NBSAE 1949-52; NSBX 1949-52; Norsk Antarktisekspedisjon 1968-69; Norsk-britisk-svenske antarktisekspedisjon; flyfoto; geografi; kartlegging; luftfoto

Vestfjella Vest: Maudheimvidda (Norsk Polarinstitutt, 1972)
Pages: Blad/Sheet B7 Place: Oslo
Keywords: Dronning Maud Land; Maudheimekspedisjonen; NBSAE 1949-52; NSBX 1949-52; Norsk Antarktisekspedisjon 1968-69; Norsk-britisk-svenske antarktisekspedisjon; flyfoto; geografi; kartlegging; luftfoto

Norwegian Antarctic Expedition, 1968-69 - Winsnes, Thore S. (Antarctic Journal of the United States, 1969)
The aim of the Norwegian Antarctic Expedition was to carry out mapping, geological and glaciological investigations of the Kraul Mts. in western Queen Maud Land. The expedition received the assistance of the National Science Foundation in the provision of American equipment and arrangements for logistics. The six member expedition, equipped for 2 1/2 months of field operations was taken by LC-130 Hercules aircraft from McMurdo to the Kraul Mts. where on several sledge journeys, covering 800 km in all, the geology of the mountains was mapped, triangulations made and base measurements taken during Nov. 22, 1968 to Jan. 20, 1969. The geology of the Kraul Mts. is rather monotonous, consisting of amygdaloid basic-to-intermediate lavas in thick, nearly flat-lying beds. An ultrabasic olivine-rich intrusive is dominant in the westernmost part of the mountains. In the east, a small isolated outcrop con sisted of sedimentary rocks in a sequence of about 50 m, containing a fossil Glossopteris flora of Permian Age. All mountains were crossed by dolerite sills and dykes. During work in the mountains, animal and plant life were observed, and some samples were taken. Core drillings were taken at the ice shelf 70 km to the N, for comparison with main basic cores.
Coordinates: S731959 S731959 W0141000 W0141000
Keywords: Dronning Maud Land; Norwegian Antarctic Expedition 1968-69; geodesi; geologi; glasiologi; kartlegging; topografi

Humboldtfjella: Fimbulheimen (Norsk Polarinstitutt, 1968)
Blad/Sheet L5
Keywords: Den Norske Antarktisekspedisjonen 1956-60; Dronning Maud Land; flyfoto; geografi; kartlegging; luftfoto

Wohlthatmassivet: Fimbulheimen (Norsk Polarinstitutt, 1968)
Blad/Sheet M5
Keywords: Den Norske Antarktisekspedisjonen 1956-60; Dronning Maud Land; flyfoto; geografi; kartlegging; luftfoto

Filchnerfjella Nord: Fimbulheimen (Norsk Polarinstitutt, 1966)
Blad/Sheet K5
Keywords: Den Norske Antarktisekspedisjonen 1956-60; Dronning Maud Land; flyfoto; geografi; kartlegging; luftfoto

Mühlig-Hofmannfjella Nord: Fimbulheimen (Norsk Polarinstitutt, 1966)
Blad/Sheet J5
Keywords: Den Norske Antarktisekspedisjonen 1956-60; Dronning Maud Land; flyfoto; geografi; kartlegging; luftfoto

Glopeflya: Fimbulheimen (Norsk Polarinstitutt, 1964)
Blad/Sheet L6
Keywords: Den Norske Antarktisekspedisjonen 1956-60; Dronning Maud Land; flyfoto; geografi; kartlegging; luftfoto

Hoelfjella Sør: Fimbulheimen (Norsk Polarinstitutt, 1964)
Blad/Sheet M6
Keywords: Den Norske Antarktisekspedisjonen 1956-60; Dronning Maud Land; flyfoto; geografi; kartlegging; luftfoto

Sydishavet og tilgrensende områder: Blad 11 - Hansen, Hans Edvard (Hvalfangernes Assuranceforening, 1964)
Place: Sandefjord
Keywords: Norsel (skip); Sørishavet; geografi; kartlegging

Kronprinsesse Märtha Kyst - Maudheimvidda: Dronning Maud Land (Norsk Polarinstitutt, 1963)
Place: [Oslo]
Keywords: Dronning Maud Land; Maudheimekspedisjonen; NBSAE 1949-52; NSBX 1949-52; Norsk-britisk-svenske antarktisekspedisjon; geografi; kartlegging

Maudheimvidda Aust: Dronning Maud Land (Norsk Polarinstitutt, 1963)
Place: Oslo
Keywords: Dronning Maud Land; Maudheimekspedisjonen; NBSAE 1949-52; NSBX 1949-52; Norsk-britisk-svenske antarktisekspedisjon; geografi; kartlegging

Borgmassivet: Maudheimvidda (Norsk Polarinstitutt, 1962)
Pages: Blad/Sheet F6 Place: Oslo
Keywords: Dronning Maud Land; Maudheimekspedisjonen; NBSAE 1949-52; NSBX 1949-52; Norsk-britisk-svenske antarktisekspedisjon; flyfoto; geografi; kartlegging; luftfoto

Filchnerfjella Sør: Fimbulheimen (Norsk Polarinstitutt, 1962)
Blad/Sheet K6
Keywords: Den Norske Antarktisekspedisjonen 1956-60; Dronning Maud Land; flyfoto; geografi; kartlegging; luftfoto

Giæverryggen: Maudheimvidda (Norsk Polarinstitutt, 1962)
Pages: Blad/Sheet F5 Place: Oslo
Keywords: Dronning Maud Land; Maudheimekspedisjonen; NBSAE 1949-52; NSBX 1949-52; Norsk-britisk-svenske antarktisekspedisjon; flyfoto; geografi; kartlegging; luftfoto

Mühlig-Hofmannfjella Sör: Fimbulheimen (Norsk Polarinstitutt, 1962)
Blad/Sheet J6
Keywords: Den Norske Antarktisekspedisjonen 1956-60; Dronning Maud Land; flyfoto; geografi; kartlegging; luftfoto

Ahlmannryggen: Fimbulheimen (Norsk Polarinstitutt, 1961)
Blad/Sheet G5
Keywords: Den norske antarktisekspedisjonen 1956-60; Dronning Maud Land; Maudheimekspedisjonen; NBSAE 1949-52; NSBX 1949-52; Norsk-britisk-svenske antarktisekspedisjon; geografi; kartlegging

H.U.Sverdrupfjella: Fimbulheimen (Norsk Polarinstitutt, 1961)
Blad/Sheet H6
Keywords: Den Norske Antarktisekspedisjonen 1956-60; Dronning Maud Land; Maudheimekspedisjonen; NBSAE 1949-52; NSBX 1949-52; Norsk-britisk-svenske antarktisekspedisjon; geografi; kartlegging

Jutulgryta: Fimbulheimen (Norsk Polarinstitutt, 1961)
Blad/Sheet H5
Keywords: Den Norske Antarktisekspedisjonen 1956-60; Dronning Maud Land; Maudheimekspedisjonen; NBSAE 1949-52; NSBX 1949-52; Norsk-britisk-svenske antarktisekspedisjon; geografi; kartlegging

Jutulgryta: Fimbulheimen (Norsk Polarinstitutt, 1961)
Blad/Sheet H5
Keywords: Den Norske Antarktisekspedisjonen 1956-60; Dronning Maud Land; Maudheimekspedisjonen; NBSAE 1949-52; NSBX 1949-52; Norsk-britisk-svenske antarktisekspedisjon; geografi; kartlegging

Jutulstraumen: Maudheimvidda (Norsk Polarinstitutt, 1961)
Blad/Sheet G6
Keywords: Den Norske Antarktisekspedisjonen 1956-60; Dronning Maud Land; Maudheimekspedisjonen; NBSAE 1949-52; NSBX 1949-52; Norsk-britisk-svenske antarktisekspedisjon; geografi; kartlegging

Kirwanveggen: Maudheimvidda (Norsk Polarinstitutt, 1961)
Blad/Sheet F7
Keywords: Den Norske Antarktisekspedisjonen 1956-60; Dronning Maud Land; Maudheimekspedisjonen; NBSAE 1949-52; NSBX 1949-52; Norsk-britisk-svenske antarktisekspedisjon; geografi; kartlegging

Neumayerskarvet: Maudheimvidda (Norsk Polarinstitutt, 1961)
Blad/Sheet G7
Keywords: Den Norske Antarktisekspedisjonen 1956-60; Dronning Maud Land; Maudheimekspedisjonen; NBSAE 1949-52; NSBX 1949-52; Norsk-britisk-svenske antarktisekspedisjon; flyfoto; geografi; kartlegging; luftfoto

Otter'n, sprækeste fly i verden: skjeggete Antarktis-flygere hjemme igjen etter vellykket kartlegging av norske ismasser - Heyerdahl, Johan Fredrik (Mannskapsavisa, 1959)
Keywords: Dronning Maud Land; ekspedisjoner; fly; kartlegging; logistikk

Norsk Polarinstitutts målevirksomhet - Luncke, Bernhard (Norsk tidsskrift for jordskifte og landmåling, 1959)
Publisher: Norges jordskiftedommer- og landmålersamband Place: Oslo
Keywords: Antarktis; botanikk; ekspedisjoner; forskning; geodesi; geologi; glasiologi; kartlegging; meteorologi; ornitologi; oseanografi; zoologi

Recent Norwegian cartographic activities in the Antarctic - Orvin, Anders K (Summary of meetings / SCAR Working Group on Cartography, 1959)
Keywords: Antarktis; kartlegging

Kartlegging i Dronning Maud Land - Bergersen, Alf (Polarboken, 1957)
Keywords: Dronning Maud Land; kartlegging

Dronning Maud Land: Sør-Rondane - Luncke, Bernhard (Norsk Polarinstitutt, 1957)
Place: [Oslo]
Keywords: Antarktiske ekspedisjon 1946-47; Dronning Maud Land; Richard Evelyn Byrd; flyfoto; geografi; kartlegging; luftfoto

Femti år for Kongen - Riiser-Larsen, Hjalmar (Gyldendal, 1957)
Keywords: Antarktis; Hjalmar Riiser; Larsen; biografier; ekspedisjoner; geografi; kartlegging; luftfart; oppdagelsesreiser; polarforskning; polarområdene

Norsk kartleggingsarbeid i Antarktis: kaptein H.E. Hansen fyller 70 år = Norwegian mapping in the Antarctic: captain H.E. Hansen reaches his 70th birthday - Ruud, Johan T (Norsk hvalfangst-tidende, 1957)
Keywords: Antarktis; Sørishavet; biografi; historie; kartlegging

Norsk-britisk-svensk vitenskapelig ekspedisjon til Antarktis 1949/52. 4 = Norwegian-British-Swedish scientific expedition to the Antarctic 1949/52. 4 - Sverdrup, Harald Ulrik (Norsk hvalfangst-tidende, 1951)
Keywords: Dronning Maud Land; Sørishavet; ekspedisjoner; fly; kartlegging

Sydishavet: Blad 2 - Hansen, Hans Edvard (Hvalfangernes Assuranceforening, 1950)
Place: Sandefjord
Keywords: Bouvetøya; Dronning Maud Land; Sørishavet; geografi; kartlegging

Notes on the sighting of land in Antarctica between 17 degr. West and 87 degr. East - Hansen, Hans Edvard (s.n., 1949)
Keywords: Antarktis; Ingrid Christensen Land; Thorshavn ekspedisjon; geografi; kartlegging; kartografi; oppdagelsesreiser

Sydishavet og tilgrensende farvann: Blad 12 - Hansen, Hans Edvard (Hvalfangernes Assuranceforening, 1949)
Place: Sandefjord
Keywords: Sørishavet; geografi; hvalfangst; kartlegging

Antarktis - Luncke, Bernhard (Norges Svalbard- og ishavs-undersøkelsers kartarbeider og anvendelsen av skrå-fotogrammer tatt fra fly, 1949)
Keywords: Antarktis; geografi; kartlegging

Marking Time; Winter in the Antarctic; The Southern Cross story; The achievement of Roald Amundsen; The conquest of Antarctica by air - Nichol, J R (Stepping stones to the South Pole, 1948)
Keywords: Antarctic (skip); Antarktis; Carsten Borchgrevink; Henrik Johan Bull; Hjalmar Riiser; Kapp Adare; Larsen; Norvegia ekspedisjonene; Roald Amundsen; Southern Cross (skip); Sydpolsekspedisjonen; kartlegging; overvintring

The Falkland Islands Dependencies Survey, 1943-46 - Wordie, James Mann (Norsk hvalfangst-tidende, 1947)
Keywords: Antarktis; Sørishavet; ekspedisjoner; forskning; kartlegging; logistikk

Antarktis/Antarctica: Kart nummer 7 - Hansen, Hans Edvard (Hvalfangernes Assuranceforening, 1946)
Place: Sandefjord
Keywords: Antarktis; Lars Christensen; ekspedisjoner; flyfoto; geografi; kartlegging; luftfoto

Sydishavet (Blad 5) - Hansen, Hans Edvard (Hvalfangernes Assuranceforening, 1946)
Place: Sandefjord
Keywords: Sørishavet; geografi; kartlegging

Sydishavet (Blad 7) - Hansen, Hans Edvard (Hvalfangernes Assuranceforening, 1946)
Place: Sandefjord
Keywords: Sørishavet; geografi; kartlegging

Sydishavet (Blad 8) - Hansen, Hans Edvard (Hvalfangernes Assuranceforening, 1946)
Place: Sandefjord
Keywords: Sørishavet; geografi; kartlegging

Atlas over dele av det antarktiske kystland = Atlas of parts of the Antarctic coastal lands - Hansen, Hans Edvard; Luncke, Bernhard (Grøndahl, 1946)
Pages: 12 s. ill., 12 kol. kart Publication Title: Atlas of parts of the Antarctic coastal lands Place: Oslo
Keywords: Antarktis; Lars Christensen; Sørishavet; Thorshavn ekspedisjon; flyfoto; kartlegging; luftfoto

Ny banke i Antarktis (Polar-årboken, 1938)
Keywords: Sørishavet; kartlegging

Kong Leopold og Dronning Astrid Land - Hoel, Adolf (Norsk Geografisk Tidsskrift - Norwegian Journal of Geography, 1938)
Publisher: Routledge
Keywords: Antarktis; ekspedisjoner; kartlegging; oppdagelsesreiser

Sydishavet - Balleny öyene (Blad 3) (Hvalfangernes Assuranceforening, 1937)
Pages: Blad 3 Place: Sandefjord
Keywords: Norvegia ekspedisjoner; Sørishavet; geografi; kartlegging

Sydishavet - Hearst Land, Charcot ö (Blad 4) (Hvalfangernes Assuranceforening, 1937)
Pages: Blad 4 Place: Sandefjord
Keywords: Norvegia ekspedisjoner; Peter I. Øy; Sørishavet; geografi; kartlegging

Sydishavet - Kong Haakon VII Hav (Blad 1) (Hvalfangernes Assuranceforening, 1937)
Pages: Blad 1 Place: Sandefjord
Keywords: Bouvetøya; Norvegia ekspedisjonene; Sørishavet; Thorshammer ekspedisjon; geografi; kartlegging

Sydishavet - Kronprins Olav Land (Blad 2) (Hvalfangernes Assuranceforening, 1937)
Pages: Blad 2 Place: Sandefjord
Keywords: Lars Christensen; Norvegia ekspedisjonene; Sørishavet; Thorshavn ekspedisjon; geografi; kartlegging

Konsul Lars Christensens ekspedisjon til Antarktis sesongen 1936-37 og dens kartografiske resultater - Hansen, Hans Edvard (Polar-årboken, 1937)
Keywords: Antarktis; ekspedisjoner; kartlegging

Sydishavet (Blad 6) - Hansen, Hans Edvard (Hvalfangernes Assuranceforening, 1937)
Pages: Blad 6 Place: Sandefjord
Keywords: Sørishavet; geografi; kartlegging

Sydishavet (Blad 7) - Hansen, Hans Edvard (Hvalfangernes Assuranceforening, 1937)
Pages: Blad 7 Place: Sandefjord
Keywords: Sørishavet; geografi; kartlegging

Sydishavet (Blad 8) - Hansen, Hans Edvard (Hvalfangernes Assuranceforening, 1937)
Pages: Blad 8 Place: Sandefjord
Keywords: Sørishavet; geografi; kartlegging

Den norske luftkartlegging i Antarktis 1937 - Romnæs, Nils; Bogen, Hans (Polar-årboken, 1937)
Keywords: Antarktis; ekspedisjoner; kartlegging

Antarktis og Sydishavet (Norwegian Mapping Authority / Kartverket, 1936)
Keywords: Antarktis; Jason ekspedisjonene; Norvegia ekspedisjoner; Odd I; Sørishavet; Thorshavn ekspedisjon; ekspedisjonen; geografi; kartlegging

Sydishavet (Blad 1) (Hvalfangernes Assuranceforening, 1936)
Pages: Blad 1 Place: Sandefjord
Keywords: Bouvetøya; Norvegia ekspedisjonene; Sørishavet; geografi; kartlegging

Atlas over Antarktis og Sydishavet : utgitt av Hvalfangernes Assuranceforening i anledning av foreningens 25-års jubileum - Hansen, Hans Edvard (red.) (Hvalfangernes Assuranceforening, 1936)
Pages: 17 bl. kart Place: Oslo
Keywords: Antarktis; Nordmenn; Norge; Sørishavet; hvalfangst; kartlegging; norske ekspedisjoner; oppdagelsesreiser

Antarktis geografi = Antarctic geography - Paulsen, Harald B (Norsk hvalfangst-tidende, 1936)
Keywords: Antarktis; geografi; kart; kartlegging; litteratur

Norske ekspedisjoners virksomhet i Antarktis - Paulsen, Harald B (Polar-årboken, 1936)
Keywords: Antarktis; Sørishavet; kartlegging

Bunnen av Weddellhavet (Hvalfangernes Assuranceforening, 1935)
Pages: Blad 1 Place: Sandefjord
Keywords: Bouvetøya; Norvegia ekspedisjoner; Sørishavet; geografi; kartlegging

Sydishavet (Blad 2) (Hvalfangernes Assuranceforening, 1935)
Pages: Blad 2 Place: Sandefjord
Keywords: Antarktis; Lars Christensen; Norvegia ekspedisjoner; Sørishavet; Thorshavn ekspedisjon; geografi; kartlegging

Sydishavet - Weddel Havet - Kong Haakon VII hav (Blad 1) (Hvalfangernes Assuranceforening, 1935)
Pages: Blad 1 Place: Sandefjord
Keywords: Bouvetøya; Norvegia ekspedisjoner; Sørishavet; geografi; kartlegging

Opdagelsen Av Ingrid Christensen Land - Mikkelsen, Klarius (Norsk Geografisk Tidsskrift - Norwegian Journal of Geography, 1935)
Publisher: Routledge
Keywords: Antarktis; Ingrid Christensen Land; Thorshavn ekspedisjon; geografi; kartlegging; kartografi; oppdagelsesreiser

Sydishavet (Blad 2) (Hvalfangernes Assuranceforening, 1933)
Pages: Blad 2 Place: Sandefjord
Keywords: Antarktis; Lars Christensen; Norvegia ekspedisjoner; Sørishavet; geografi; kartlegging

Sydishavet (Blad 3) (Hvalfangernes Assuranceforening, 1933)
Pages: Blad 3 Place: Sandefjord
Keywords: Antarktis; Sørishavet; ekspedisjoner; geografi; kartlegging

Sydishavet - Weddel Havet - Kong Haakon VII hav (Blad 1) (Hvalfangernes Assuranceforening, 1933)
Pages: Blad 1 Place: Sandefjord
Keywords: Bouvetøya; Norvegia ekspedisjoner; Sørishavet; geografi; kartlegging

Norvegia-ekspedisjonen 1930-1931 (Norges geografi oppmåling, 1931)
Pages: 5 kart Place: [S.l.]
Keywords: Antarktis; Bouvetøya; Norvegia ekspedisjoner; Sørishavet; geografi; kartlegging

Sydishavet - Kong Haakon VII hav (Norges geografi oppmåling, 1931)
Place: [S.l.]
Keywords: Antarktis; Sørishavet; ekspedisjoner; geografi; kartlegging

The "Norvegia" Antarctic expedition of 1929-1930 - Long, A T (The Hydrographic Review, 1931)
Keywords: Antarktis; Dronning Maud Land; Sørishavet; ekspedisjoner; geografi; kartlegging; logistikk; oseanografi

The Antarctic (The Geographical Journal, 1930)
Publisher: [Wiley, Royal Geographical Society (with the Institute of British Geographers)]
Keywords: Antarktis; Bouvetøya; Christen Christensen; Hjalmar Riiser; Larsen; Norvegia ekspedisjonen; Peter I. Øy; kartlegging; oppdagelsesreiser

Våre polarflyverferder i nord og syd - Arnesen, Odd (Til veirs på norske vinger : av flyvningens historie i Norge, 1930)
Keywords: Antarktis; Bouvetøya; Finn Lützow; Hjalmar Riiser Larsen; Holm; Nordmenn; Norge; Norvegia ekspedisjonen; biografier; historie; kartlegging; luftfart

Antarctic discoveries - Brown, R N Rudmose (Scottish Geographical Magazine, 1930)
Publisher: Routledge
Keywords: Bouvetøya; Norvegia ekspedisjonene; Sørishavet; kartlegging; oppdagelsesreiser

Den Tredje »Norvegia«-Ekspedisjon 1929—1930 - Riiser-Larsen, Hjalmar (Norsk Geografisk Tidsskrift - Norwegian Journal of Geography, 1930)
Publisher: Routledge
Keywords: Bouvetøya; Hjalmar Riiser; Larsen; Norvegia ekspedisjonen; geografi; kartlegging

[Kart over Antarktika og Sydishavet]. Skisser med "Odd" og "Norvegia" sine ruter i Antarktis 1927-1929 - [Aagaard, Bjarne] (1929)
Keywords: Antarktis; Norvegia ekspedisjoner; Odd I; Sørishavet; ekspedisjonen; geografi; kartlegging

Peter I Øy - Larsen, Nils (1929)
Pages: ved Nils Larsen, Norvegia-Ekspedisjonen 1928-1929 Place: Oslo
Keywords: Lars Christensen; Norvegia ekspedisjonen; Peter I. Øy; geografi; kartlegging

Fra det norske forskningsarbeide i de vest-antarktiske strøk syd-sommeren 1927—28 - Holtedahl, Olaf (Norsk Geografisk Tidsskrift - Norwegian Journal of Geography, 1928)
Publisher: Routledge
Keywords: Lars Christensen; Odd I; Peter I. Øy; ekspedisjonen; geografi; kartlegging

Noen bemerkninger om 'Odd I' -ekspedisjonens naturvidenskabelige materiale - Holtedahl, Olaf (Norsk Geografisk Tidsskrift - Norwegian Journal of Geography, 1927)
Publisher: Det Norske Geografiske Selskab
Keywords: Lars Christensen; Odd I; Peter I. Øy; ekspedisjonen; ekspedisjoner; geografi; kartlegging; oppdagelsesreiser

Odd I’s tokt til Peter den Førstes Ø. Beretning om den av konsul Lars Christensen 1 Januar 1927 utsendte ekspedisjon - Tofte, Eyvind (Norsk Geografisk Tidsskrift - Norwegian Journal of Geography, 1927)
Publisher: Det Norske Geografiske Selskab
Keywords: Lars Christensen; Odd I; Peter I. Øy; ekspedisjonen; ekspedisjoner; geografi; kartlegging; oppdagelsesreiser

Produksjon av satellittbildekart fra Dronning Maud Land, Antarktis - Amlien, Jostein; Luktvasslimo, Brit Åse (Norsk Polarinstitutt)
Keywords: Dronning Maud Land; kartlegging; kartografi; satellite bilder

Parry Mountains - Collier, William; Borchgrevink, Carsten Egeberg
Pages: [Blad EE8] Place: [S.l.]
Keywords: Antarktis; Southern Cross; ekspedisjonen; geografi; kartlegging

Robertson Bay, South Victoria Land - Collier, William; Borchgrevink, Carsten Egeberg
Pages: [Blad E11] Place: [S.l.]
Keywords: Antarktis; Southern Cross; ekspedisjonen; geografi; kartlegging

Southern Cross from Hobart to Cape Adare - Collier, William; Borchgrevink, Carsten Egeberg
Pages: [Blad E9] Place: [S.l.]
Keywords: Antarktis; Carsten Egeberg Borchgrevink; Kapp Adare; Southern Cross; ekspedisjonen; geografi; kartlegging

Journal over flyvninger utført under Lars Christensens ekspedisjon 1936/37 - Romnæs, Nils
Pages: 3 s. Place: [Oslo]
Keywords: Antarktis; Thorshavn ekspedisjon; flyfoto; flyvninger; kartlegging; luftfoto